Knowledge, attitude, practice, needs, and implementation status of intensive care unit staff toward continuous renal replacement therapy: a survey of 66 hospitals in central and South China - Xiaoyan Yu; Lin Ouyang; Jinxiu Li; Ying Peng; Dingming Zhong; Huan Yang; Yanyan Zhou (BMC, 2024)
Abstract Background Continuous renal replacement therapy (CRRT) is a commonly utilized form of renal replacement therapy (RRT) in the intensive care unit (ICU). A specialized CRRT team (SCT, composed of physicians and nurses) engage playing pivotal roles in administering CRRT, but there is paucity of evidence-based research on joint training and management strategies. This study armed to evaluate the knowledge, attitude, and practice (KAP) of ICU staff toward CRRT, and to identify education pathways, needs, and the current status of CRRT implementation. Methods This study was performed from February 6 to March 20, 2023. A self-made structured questionnaire was used for data collection. Descriptive statistics, T-tests, Analysis of variance (ANOVA), multiple linear regression, and Pearson correlation coefficient tests (α = 0.05) were employed. Results A total of 405 ICU staff from 66 hospitals in Central and South China participated in this study, yielding 395 valid questionnaires. The mean knowledge score was 51.46 ± 5.96 (61.8% scored highly). The mean attitude score was 58.71 ± 2.19 (73.9% scored highly). The mean practice score was 18.15 ± 0.98 (85.1% scored highly). Multiple linear regression analysis indicated that gender, age, years of CRRT practice, ICU category, and CRRT specialist panel membership independently affected the knowledge score; Educational level, years of CRRT practice, and CRRT specialist panel membership independently affected the attitude score; Education level and teaching hospital employment independently affected the practice score. The most effective method for ICU staff to undergo training and daily work experience is within the department. Conclusion ICU staff exhibit good knowledge, a positive attitude and appropriately practiced CRRT. Extended CRRT practice time in CRRT, further training in a general ICU or teaching hospital, joining a CRRT specialist panel, and upgraded education can improve CRRT professional level. Considering the convenience of training programs will enhance ICU staff participation. Training should focus on basic CRRT principles, liquid management, and alarm handling.